2019
DOI: 10.1002/ecy.2781
|View full text |Cite
|
Sign up to set email alerts
|

The unprecedented loss of Florida's reef‐building corals and the emergence of a novel coral‐reef assemblage

Abstract: Over the last half century, climate change, coral disease, and other anthropogenic disturbances have restructured coral‐reef ecosystems on a global scale. The disproportionate loss of once‐dominant, reef‐building taxa has facilitated relative increases in the abundance of “weedy” or stress‐tolerant coral species. Although the recent transformation of coral‐reef assemblages is unprecedented on ecological timescales, determining whether modern coral reefs have truly reached a novel ecosystem state requires evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 78 publications
3
84
0
2
Order By: Relevance
“…Although retaining some of their geomorphic character, these once easy to differentiate geomorphic zones are now more difficult to separate based on coral cover or other ecological indices. This difficulty stems from the functional loss of major reef builders such as Acroporids (e.g., A. palmata, A. cervicornis ) which are largely responsible for long-term accretion in shallow Caribbean reefs ( Macintyre & Glynn, 1976 ; Blanchon et al, 2017 ; Toth et al, 2019 ). These losses were likely driven by multiple strikes from major Hurricanes that crossed the study area (Allen in 1980; Gilbert in 1988; Emily in 2005 and Wilma in 2005), and their coincident timing with white band/pox epidemics that were decimating acroporids elsewhere ( Gladfelter, 1982 ; Lewis, 1984 ; Aronson & Precht, 2001 ; Bruckner, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although retaining some of their geomorphic character, these once easy to differentiate geomorphic zones are now more difficult to separate based on coral cover or other ecological indices. This difficulty stems from the functional loss of major reef builders such as Acroporids (e.g., A. palmata, A. cervicornis ) which are largely responsible for long-term accretion in shallow Caribbean reefs ( Macintyre & Glynn, 1976 ; Blanchon et al, 2017 ; Toth et al, 2019 ). These losses were likely driven by multiple strikes from major Hurricanes that crossed the study area (Allen in 1980; Gilbert in 1988; Emily in 2005 and Wilma in 2005), and their coincident timing with white band/pox epidemics that were decimating acroporids elsewhere ( Gladfelter, 1982 ; Lewis, 1984 ; Aronson & Precht, 2001 ; Bruckner, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Levels were: (a) key reef-building species (key spp. ), consisting of large branching Acroporids and massive Orbicella (formerly Montastrea ) “ annularis ” complex ( Budd et al, 2012 ), which are considered to be the principal reef builders in the Caribbean ( Goreau, 1959 ; Lewis, 1984 ; Toth et al, 2019 ) and (b) less influential species like small massive, sub-massive or encrusting, digitate and foliose morphologies with lower growth rates, which participate in the accretion processes but are less represented in the geological records. This group includes some abundant species in the contemporary coral communities like Agaricia agaricites and Porites astreoides ( Aronson, 2006 ; González-Barrios & Álvarez Filip, 2018 ; Toth et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent coring studies have shown that the reefs of the Florida Keys stopped accreting 3,000 years ago, and that the species assemblages have changed from the traditional reef-building species (A. palmata and Orbicella spp.) to weedier species such as Porites astreoides and Siderastrea siderea (Toth et al, 2018(Toth et al, , 2019. Similar to elsewhere in the Caribbean, significant losses of the Acroporid species caused mainly by disease, and hurricanes in the 1980s led to a considerable reduction in coral cover on the shallow forereefs.…”
Section: United Statesmentioning
confidence: 99%
“…In a few short years, the ecological extirpation of many key charismatic species has fundamentally changed the way reefs throughout south Florida look and function, resulting in a depauperate community of small, ephemeral, stress-tolerant species (Burman et al 2012, Precht et al 2016, Toth et al 2019. In addition, the conservation of species-specific disease susceptibility traits, region-wide, suggests that local management efforts aimed at improving reef resilience todate have been ineffective at preventing and minimizing the impacts of coral disease outbreaks.…”
Section: Management Responsibilitymentioning
confidence: 99%